Elementary Geometry for College Students (6th Edition)

Published by Brooks Cole
ISBN 10:
ISBN 13:

Chapter 10 - Section 10.5 - Equations of Lines - Exercises - Page 472: 39

Answer

(6, 0)

Work Step by Step

Equating the expressions for y: $\frac{1}{3}x-2=\frac{1}{2}x-3$ $1=\frac{1}{6}x$ $x=6$ Substituting $x=6$ into $y=\frac{1}{3}x-2$: $y=\frac{1}{3}*6-2$ $y=\frac{6}{3}-2$ $y=2-2$ $y=0$ So the answer is $(6, 0)$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.